2021
DOI: 10.2528/pier21051703
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hermitian Electromagnetic Metasurfaces at Exceptional Points (Invited Review)

Abstract: Exceptional points are spectral singularities in non-Hermitian systems at which two or more eigenvalues and their corresponding eigenvectors simultaneously coalesce. Originating from quantum theory, exceptional points have attracted significant attention in optics and photonics because their emergence in systems with nonconservative gain and loss elements can give rise to many counterintuitive phenomena. Metasurfaces -two-dimensional artificial electromagnetic materials structured at the subwavelength scale -c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(24 citation statements)
references
References 117 publications
0
24
0
Order By: Relevance
“…For example, eigenvectors of a non-Hermitian Hamiltonian do not require to be orthogonal, and at certain points in the parameter space called exceptional points (EPs), two eigenvectors, as well as their eigenvalues, coalesce. Metasurfaces provide an excellent arena for exploring the underlying physics of non-Hermitian systems because they can be engineered with precise control over the structural parameters that govern resonator properties and easily be measured by standard optical reflection or transmission. Recently, PT-symmetric metasurfaces and their topological features of non-Hermitian matrices near EPs have been investigated; for example, Genevet et al demonstrated that by precisely designing the sizes of Al nanoantennas, a planar chiral plasmonic metasurface exhibits 2π topological phase accumulation distributed along any arbitrarily closed parameter loop encircling the EP in a reflection regime . Up to now, however, most of the works have focused on plasmonic metasurfaces, wherein the phenomena related to non-Hermitian properties such as anomalous transparency, unidirectional transmission, power oscillation, , and so on mainly arise from electric dipolar scattering and decaying of metallic nanoantennas, completely irrespective of other orders of resonant modes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, eigenvectors of a non-Hermitian Hamiltonian do not require to be orthogonal, and at certain points in the parameter space called exceptional points (EPs), two eigenvectors, as well as their eigenvalues, coalesce. Metasurfaces provide an excellent arena for exploring the underlying physics of non-Hermitian systems because they can be engineered with precise control over the structural parameters that govern resonator properties and easily be measured by standard optical reflection or transmission. Recently, PT-symmetric metasurfaces and their topological features of non-Hermitian matrices near EPs have been investigated; for example, Genevet et al demonstrated that by precisely designing the sizes of Al nanoantennas, a planar chiral plasmonic metasurface exhibits 2π topological phase accumulation distributed along any arbitrarily closed parameter loop encircling the EP in a reflection regime . Up to now, however, most of the works have focused on plasmonic metasurfaces, wherein the phenomena related to non-Hermitian properties such as anomalous transparency, unidirectional transmission, power oscillation, , and so on mainly arise from electric dipolar scattering and decaying of metallic nanoantennas, completely irrespective of other orders of resonant modes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, non-Hermitian physics has attracted great attention owing to its rich physical significances and various practical applications [1][2][3][4]. Exceptional point (EP) is a unique feature for non-Hermitian systems, which has become a hot topic in photonics [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], mechanics [20][21][22][23][24][25][26], and acoustics [27][28][29][30][31][32][33][34][35][36][37][38][39] owing to its great potential in energy transport. In acoustics, based on parity-time symmetric systems [27][28][29][30][31][32], researchers have realized EP by introducing balanced gain and loss which can be obtained by a pair of electro-acoustic resonators loaded with specifically tailored circuits [30] and by a composite structure composed of...…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Owing to the dissipative nature of heat transfer, its effective Hamiltonian or scattering matrix [20] turns out to be non-Hermitian. Non-Hermitian wave systems show many unusual symmetric and topological properties [21,22] such as unidirectional transparency, [23] coherent perfect absorption, [24] single-mode lasing, [25] and skin effect. [26] Thus inspired, some thermal systems were also developed to study the topology of heat transfer.…”
Section: Introductionmentioning
confidence: 99%